Discrimination of geographical origins of Chinese acacia honey using complex 13C/12C, oligosaccharides and polyphenols. (30th January 2019) - She, Seng; Chen, Lanzhen; Song, Hongbo; Lin, Guanghui; Li, Yi; Zhou, Jinhui; Liu, Cuiling
Highlights: Chinese acacia honey from different geographical origins were discriminated. The δ 13 C value of glucose and fructose could be identified as useful marker. Acacia honey samples were from the main producing regions of China. Abstract: The aim of this study was to predict the geographical origin of acacia honey of China through analysis of physicochemical parameters combination with chemometrics. Samples from six different origins were investigated on parameters of δ 13 C value, oligosaccharides and polyphenols, using EA-IRMS/LC-IRMS, GC–MS and HPLC–MS, respectively. The results indicated that the δ 13 C value of honey from Gansu region were lower than those of other regions. Oligosaccharides of honey from Shanxi and Shaanxi regions were both higher than other four regions. Polyphenols of honey from Shandong region was the highest and were better parameters than both δ 13 C and oligosaccharides in discrimination of geographical origins. Partial Least Square Discriminant Analysis (PLS-DA) showed that when all 31 different parameters were combined, a correct classification rate of 94.12% could be achieved using external cross validation method. In conclusion, the method in discrimination of geographical can be used to provide reliable and useful reference information.